Discussion of “Are Related Party Transactions Red Flags?” - Jorgensen, Bjorn N.; Morley, Julia (Contemporary Accounting Research, 2017)
Abstract Kohlbeck and Mayhew ( ) create a new data set featuring two types of related party transactions. They use empirical‐archival methods to investigate the effect of such transactions on the likelihood of restatements and on audit fees. Their findings suggest that related party transactions related to directors, officers and major shareholders are associated with poor “tone at the top” and that this leads management to negotiate for lower‐quality audits to minimize monitoring costs. To offer avenues for future research, we focus our discussion on three aspects of their paper related to causality, definitions of variables, and generalizability to non‐U.S. jurisdictions.